O vitae experientia dux. Die Rolle der Erfahrung im theoretischen und praktischen Weltbezug des frühen Humanismus und ihre Konsequenzen - Keßler, Eckhard (Das Mittelalter, 2012)
Abstract The essay is divided into five sections: the first section gives a short overview of the history of “experience” – Greek empeiria, Latin experientia – which takes Aristotle’s theory of knowledge as its starting point. Within its theoretical framework, experience served as a crucial mediator between sensory perception and intellectual knowledge. In the philosophy of Late Antiquity and the High Middle Ages the category of experience then was reduced to marginal importance under neo-Platonic and Arabic influences. At the dusk of the Middle Ages, however, it was rehabilitated and turned into a rallying cry by those who attempted to overcome late medieval philosophy. The following section describes the revaluation of experience as the fountain of real knowledge under the auspices of Petrarchism, which ran contrary to the formalistic teachings of the Scholastics. The remaining sections first deal with the role of the humanist concept of experience in the field of moral philosophy (specifically regarding the teaching of history). Secondly, it shows how experience worked as an incentive for field research in natural history and medicine and how it precipitated a revival of ancient Aristotelian empiricism within natural philosophy, thereby paving the way for the modern empirical science of nature.